Analysis of Phosphorus on Prill and Liquid Fertilizer - Dita Rahmawati; Khoirriah Widyasari (Universitas Negeri Yogyakarta, 2022)
The research was conducted on the determination of the levels of phosphorus on prill and liquid fertilizers using the UV-Visible method compared with Indonesian National Standard (SNI 02-2801-2010). Phosphorus is the most important nutrient for crop to gain the high productivity. The sample of the research were prill and liquid fertilizer that had SNI. Phosphorus levels in NPK fertilizer were analyzed using the UV-Vis spectrophotometer method. The result was an analysis of phosphorus levels in prill fertilizers of 14,67% and phosphorus levels in liquid fertilizers of 18,55%. These results are in accordance with the Indonesian National Standard (SNI) 2803:2010, which is a minimum phosphorus content of 8%.